Rencana Strategis Pengembangan Mie Pt Rasaraya Untuk Meningkatkan Kualitas Mie Terbaik Di Era Modern - Deyvanda Deyvanda (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This strategic plan is developed as PT. Rasaraya Food initiative to enhance the competitiveness of its noodle products in the global market through quality improvement, innovation, and market expansion. In response to the growing global consumption of instant noodles, the company emphasizes the need for an integrated strategy, incorporating internal and external analyses using SWOT and PESTEL frameworks. The proposed strategies include upgrading product quality to meet international standards, strengthening innovation with healthy and eco-friendly variants, utilizing digital technology for global distribution, and implementing sustainable business practices. The document also highlights challenges such as limited export experience and the need for skilled human resources at the global level. The implementation plan focuses on gradual market expansion, investment in R&D, digitalization, and strategic partnerships. This strategic direction is expected to position PT. Rasaraya as a key player in a competitive, innovative, and sustainable global noodle industry.